2003
DOI: 10.1034/j.1399-0039.2003.00107.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA‐B27 polymorphism in the Malays

Abstract: The frequency of HLA-B27 and its subtypes was determined in 878 Malay subjects. Thirty-five of the subjects typed for HLA-A, -B and -DR were found to be positive for HLA-B27. The frequency of this allele in the Malay population was found to be 3.99%. The subtypes observed and their frequencies are: HLA-B*2704 (19.4%), HLA-B*2705 (5.6%), HLA-B*2706 (72.2%) and HLA-B*2707 (2.8%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 15 publications
4
20
0
Order By: Relevance
“…Our observations are consistent with HLA data obtained from previous studies on the Malays [13][14][15][16][17], which corroborate historical data, archaeological evidence, linguistic, and mtDNA studies reported previously [4 -12]. Further studies on the HLA of other Malay subethnic groups in the Malay Archipelago should therefore clarify the origin and genetic relationships between them, as well as with other world populations.…”
Section: Discussionsupporting
confidence: 92%
“…Our observations are consistent with HLA data obtained from previous studies on the Malays [13][14][15][16][17], which corroborate historical data, archaeological evidence, linguistic, and mtDNA studies reported previously [4 -12]. Further studies on the HLA of other Malay subethnic groups in the Malay Archipelago should therefore clarify the origin and genetic relationships between them, as well as with other world populations.…”
Section: Discussionsupporting
confidence: 92%
“…Such information is helpful for identifying the differences thay may lead to better understanding of disease mechanisms. [13][14] HLA has an important role in population genetics, donor selection for organ transplantation, paternity determination, various infectious and autoimmune diseases association, clinical utility in understanding drug reactions (antiretroviral, antiepileptic etc). Overall biological relevance to adaptive immunity and vaccine development demands extensive knowledge of HLA variations among populations.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the frequency of B*27 corresponds to the incidence of AS in the worldwide population. It is clearly a risk factor attributed to the susceptibility of the disease and proven to be a useful genetic marker for the diagnosis of the disease (Gonzalez‐Roces et al ., 1997; Feltkamp et al ., 2001; Dhaliwal et al ., 2003; Yang et al ., 2004; Park et al ., 2008). Naturally, discovery of a new B27 allele extends a kin interest on its likely association with AS.…”
Section: Introductionmentioning
confidence: 99%